Parliament Opposition Strategy in Indonesia (Case Study of Gerindra Party During Joko Widodo and Jusuf Kalla's Era 2014-2019) - Rachman, Muhammad Ridho; Wardhani, Sri Budi Eko (Jurnal Politik Indonesia: Indonesian Political Science Review, 2020)
This research analyzes parliament opposition in Indonesia by Gerindra Party (2014-2019) as a party whose consistently outside the government and functioning as an opposition party. How is it implemented, and what kind of strategy Gerindra performs to influence the parliamentary decision-making process? To answer this, the study uses qualitative methods by collecting data through literature review, data tracking, and in-depth interviews. The theoretical perspective in this research used Steinack's argument about the opposition strategy who states that the behavior of the opposition party in parliament is the accumulation of the impact of the structural and institutional factors, socio-demographic, and party’s informal rules of engagement. The research found that as an opposition party, Gerindra focuses on content-oriented strategies using the area of public policymaking as a medium of political interplays such as at the commission level or other work units.